2016
DOI: 10.1088/2053-1583/3/3/031007
|View full text |Cite
|
Sign up to set email alerts
|

Environmental effects in mechanical properties of few-layer black phosphorus

Abstract: We report on the mechanical properties of few-layer black phosphorus (BP) nanosheets, in high vacuum and as a function of time of exposure to atmospheric conditions [1]. BP flakes with thicknesses ranging from 4 to 30 nm suspended over circular holes are characterized by nanoindentations using an atomic force microscope tip. From measurements in high vacuum an elastic modulus of 46±10 GPa and breaking strength of 2.4±1 GPa are estimated. Both magnitudes are independent of the thickness of the flakes. Our resul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 40 publications
(52 reference statements)
3
29
1
Order By: Relevance
“…The ideal elastic moduli of zigzag and armchair BP nanoribbons are approximately 65 and 27 GPa, respectively [26]. Morenomoreno et al [67] investigated the effects of environmental conditions on the mechanical properties of few-layer BP, and the results indicated that the elastic modulus and the breaking strength of BP nanosheets were 46 ± 10 GPa and 2.1 ± 1 GPa, respectively. The in-plane Young's modulus of single-layer BP was 41.3 GPa in the direction perpendicular to the pucker and 106.4 GPa in the parallel direction, and the ideal strains were 0.48 and 0.11 in the perpendicular and parallel directions, respectively [68].…”
Section: Potential Of Bp As Lubricantsmentioning
confidence: 99%
“…The ideal elastic moduli of zigzag and armchair BP nanoribbons are approximately 65 and 27 GPa, respectively [26]. Morenomoreno et al [67] investigated the effects of environmental conditions on the mechanical properties of few-layer BP, and the results indicated that the elastic modulus and the breaking strength of BP nanosheets were 46 ± 10 GPa and 2.1 ± 1 GPa, respectively. The in-plane Young's modulus of single-layer BP was 41.3 GPa in the direction perpendicular to the pucker and 106.4 GPa in the parallel direction, and the ideal strains were 0.48 and 0.11 in the perpendicular and parallel directions, respectively [68].…”
Section: Potential Of Bp As Lubricantsmentioning
confidence: 99%
“…[6][7][8][9] Theoretical calculations predict different interesting properties for this material: an electronic structure with a bandgap in the ultrafast optoelectronics applications range, 6,10,11 high carrier mobilities, 12,13,14 topological behavior 15,16 and optical properties 17,18 that would make antimonene suitable for numerous optoelectronics applications, ranging from solar cell and light-emitting devices to touch screens and photodetectors, [17][18][19][20][21] but without the above mentioned instability of isolated layers of black phosphorus, which are highly hygroscopic (they tend to take up moisture from air) degrading in a few hours of exposition, which limits their application. 22,23 Recent studies have shown both experimentally and theoretically that insights into the optical properties of few-layer antimonene based on Raman spectroscopy are hampered. 6,7 Tsai et al…”
mentioning
confidence: 99%
“…115 When compared to other 2DLMs with similar honeycomb structures, such as graphene, 4 graphane, 111 WS 2 , 84 MoS 2 69 and h-BN, 133 the weaker P-P bond strength and compromised dihedral angles made the ideal Young's modulus of phosphorene (0.166 TPa in the zigzag direction and 0.044 TPa in the armchair direction) at 0 K much smaller. Besides, the pretension of few-layer black phosphorus was determined experimentally to be in the range of 0.05-0.44 N m −1 , 83,93 and thicker nanosheets had smaller values because of their stronger structural stiffness. Interestingly, phosphorene has a negative Poisson's ratio of −0.027 in the out-of-plane direction when the strain is applied in the zigzag direction due to the coupling hinge mechanism where the hinge θ 546 and θ 214 in Fig.…”
Section: Elastic Propertiesmentioning
confidence: 98%
“…Similarly, the deformation consists of linear elastic response under small loads and nonlinear elastic response under larger loads. Thus the effective spring constant of 2D nanosheets under small loads could also be used for the extraction of E and T. 85,92,93 When taking the size of the indenter into consideration, the force-displacement equation could be further modified. 50 In addition to Young's modulus and pretension, breaking strength can also be derived from the model of a clamped circular membrane under a point load.…”
Section: δP¼mentioning
confidence: 99%
See 1 more Smart Citation